Procrastinación y rendimiento académico en estudiantes de medicina, con dependencia a dispositivos móviles en una universidad pública, Iquitos – 2023 - Peña Chapilliquen, Claudio (2024)
Objective: To determine the level of procrastination and low academic performance in medical students with dependence on mobile devices at a public university in Iquitos, period 2023. Material and methods: An analytical, cross-sectional study was carried out in which 89 medical students were included, according to selection criteria which were divided according to the degree of dependence on mobile devices, the chi square was calculated. Results: No significant differences were observed regarding the variables age, sex, origin or cycle of studies between patients with high, medium or low dependence (p>0.05); The degree of dependence on mobile devices in medical students was: high (17%); medium (15%) and low (68%); The degree of procrastination in medical students was: high (10%); medium (52%) and low (38%); the prevalence of low academic performance in medical students was 7%; There is an association between the degree of dependence on mobile devices and procrastination in medical students (p<0.05). Conclusion: Conclusion: the level of procrastination in medical students was predominantly medium level (52%), the prevalence of low academic performance in medical students was 7%, the level of dependence on mobile devices is associated with procrastination and low academic performance in medical students.